Chemometric analysis of monoterpenes and sesquiterpenes of conifers - Bakó, Eszter; Böszörményi, Andrea; Vargáné Szabó, Bettina; Engh, Marie Anne; Hegyi, Péter; Ványolós, Attila; Csupor, Dezső (Frontiers in Plant Science, 2024)
Volatile organic compounds (VOCs) and essential oils of conifers are widely used in the pharmaceutical industry. This work aimed to analyze the VOCs of 30 conifer species representing the Pinaceae and Cupressaceae families. Samples were collected from arboreta in Hungary, and their chemical composition was determined by gas chromatography (SPME-GC/MS); then, chemometric analyses were performed using multivariate methods to identify characteristic VOCs of conifers. Here, we present results for monoterpene and sesquiterpene profiles of the examined conifer samples. The most abundant compounds detected were α-pinene, bornyl acetate, limonene, β-pinene, β-caryophyllene, β-myrcene, δ-3-carene, and β-phellandrene. The results showed that the following volatiles were characteristic of the conifer groups: sabinene (RRT=6.0) for the cupressoid group (which includes the Cupressaceae species), longifolene (RRT=15.0) and β-pinene (RRT=6.1) were characteristic of the pinoid group (including Picea, Pinus, and Pseudotsuga species), and camphene (RRT=5.5) and bornyl acetate (RRT=12.6) were characteristic of the abietoid group (including Abies, Cedrus, and Tsuga species). Our results on VOCs in the Pinaceae and Cupressaceae families contribute to the elucidation of biodiversity patterns of conifer species and, in addition, may support the industrial application of terpenes.